Coordination of the Service of Investment and One Stop Service with the Tourism Service in Licensing of Karaoke Tourism Business in Medan City - Muhammad Fadhli Nasution; Simson Ginting (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2023)
The problems found in this study are communication between agencies that are still not running well, limited resources to supervise tourism business licenses in Medan City, overlapping authority between agencies, resulting in each agency waiting for each other to misuse tourism business licenses and the discovery of indications of abuse of authority in the implementation of tourism business license supervision in Medan City. This type of research is descriptive research using qualitative methods. The data collected is in the form of words, images, and not numbers. The sampling technique to explore information that will be the basis of this study is the purposive sampling technique. To perform validation of found information using data triangulation. The results showed that the coordination between the Investment Office and One-Stop Integrated Services and the Medan City Tourism Office was no longer in the process before the issuance of permits but after the issuance of permits. Unification of actions taken by the Investment Office and One-Stop Integrated Services and the Medan City Tourism Office has been carried out, namely the enforcement of strict sanctions against karaoke business owners who violate the rules in accordance with Standard Operating Procedures, then communication is carried out by exchanging information related to karaoke tourism business licenses in Medan City and communication is carried out if there is a karaoke business license that does not match between the Business Identification Number (NIB) and Business carried out in the field. The distribution of tasks carried out in coordination with karaoke business licensing has run optimally. Supervision and enforcement related to tourism business licenses, especially karaoke, are in accordance with established rules, but there are still some karaoke places that are still operating even though they have received a reprimand or revocation of their business licenses.